THE INFLUENCE OF COMPENSATION ON EMPLOYEE PERFORMANCE MEDIATED BY JOB SATISFACTION AT DR. RM. DJOELHAM GENERAL HOSPITAL, BINJAI CITY - Netty Arliza; Mesra B (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The aim of this research was to determine and analyze the influence of compensation on employee performance, both directly and indirectly, through job satisfaction at Dr. RM. Djoelham General Hospital in Binjai City. The type of research was quantitative associative. The population in this study consisted of 357 employees, with a sample size of 78 employees. The data collection technique used was distributing questionnaires. Data analysis in this research was conducted using the Structural Equation Model PLS with the assistance of the Smart PLS 3.0 application tool. The results of this study indicated that: (1) Compensation had a positive and significant influence on employee performance with a t-statistic value of 11,743, which is greater than the t-table (1.96), and a P-Value of 0,000, which is less than the significance level (0.05). (2) Compensation had a positive and significant influence on job satisfaction with a t-statistic value of 34,236, which is greater than the t-table (1.96), and a P-Value of 0,000, which is less than the significance level (0.05). (3) Job satisfaction had a positive and significant influence on employee performance with a t-statistic value of 4,761, which was greater than the t-table (1.96), and a P-Value of 0,000, which was less than the significance level (0.05). (4) Compensation had a positive and significant influence on employee performance through job satisfaction with a t-statistic value of 4,680, which was greater than the t-table (1.96), and a P-Value of 0,000, which was less than the significance level (0.05), indicating that job satisfaction can mediate the relationship between compensation and employee performance at Dr. RM. Djoelham General Hospital, Binjai City.